Edukasi Peran Gizi Dalam Pencegahan Anemia Gizi Besi Pada Remaja Putri Markaz Tahfiz Alquran Al-Fityan School Aceh - Dini Junita; Farah Fajarna (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Anemia is one of the nutritional problems in adolescents that can be prevented from an early age. Education on the role of nutrition in preventing iron deficiency anemia in young women is one of the efforts that can be made to provide accurate information regarding this problem. So that teenagers are more concerned about their health, especially what they consume and other habits that can increase the risk of anemia. This community service activity was carried out at Markaz Tahfiz Alquran Alfityan School Banda Aceh. This community service activity aims to provide education to female students about anemia and the role of nutrition in preventing iron deficiency anemia. Based on community service activities at Markaz Tahfiz Alquran Alfityan School Aceh, it was concluded that as many as 31 female students took part in activities providing education on the role of nutrition in preventing iron deficiency anemia in young women. Based on verbal and written observations and evaluations, female students were able to receive and understand the material well, there was an increase in knowledge of 2.4 points. Based on the results obtained from this activity, it is recommended that adolescent health promotion be carried out more intensively in education centers.